2022
DOI: 10.1007/s10834-021-09814-z
|View full text |Cite
|
Sign up to set email alerts
|

Household Spending Patterns and Hardships during COVID-19: A Comparative Study of the U.S. and Israel

Abstract: The combined supply and demand shocks of the COVID-19 pandemic have created the largest consumer behavior shift in recent history, while exposing millions of households to material hardships like food insecurity and housing instability. In this study, we draw on national surveys conducted early in the pandemic to investigate the pandemic's effects on selfreported consumer spending behaviors and experiences of hardship for households in the US and Israel; two countries that are similar in terms of their develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Despite its global reach, countries had different experiences with and different response to the pandemic. Providing a national context for understanding the impact of the pandemic, Roll et al ( 2022 ) conducted a comparative analysis of household spending and hardship in the US (collected April-May 2020) and Israel (collected June-July 2020). The researchers found several similarities between the countries, including stable housing expenditures but more volatile food and credit card payment expenditures.…”
Section: Sociodemographic Disparities In Covid-19 Impactmentioning
confidence: 99%
“…Despite its global reach, countries had different experiences with and different response to the pandemic. Providing a national context for understanding the impact of the pandemic, Roll et al ( 2022 ) conducted a comparative analysis of household spending and hardship in the US (collected April-May 2020) and Israel (collected June-July 2020). The researchers found several similarities between the countries, including stable housing expenditures but more volatile food and credit card payment expenditures.…”
Section: Sociodemographic Disparities In Covid-19 Impactmentioning
confidence: 99%
“…The pandemic, and the restrictive measures taken to control the pandemic, have often led to uncertainty in demand and supply disruptions, which have ultimately affected product prices and household food consumption. In addition, containment measures such as isolation, maintaining social distancing, closing businesses, and closing borders have led to a sharp decline in economic activity, affecting household income and consumer behavior [ 16 , 17 ], which is once again reflected in household expenditures. Although food is a basic necessity, nevertheless, food consumption is not immune to this type of crisis.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, Roll et al . (2022) noted less dramatic effects in overall spending (9.6 per cent), where there was a shift away from goods and services (−7.7 per cent) towards durables (+6.7 per cent). Other studies reported that households also grew their savings over this period.…”
Section: Household Consumption During the Pandemicmentioning
confidence: 99%